2020
DOI: 10.1039/d0tc02076a
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the preferred orientation of layered BiOI solar absorbers

Abstract: Bismuth oxyiodide has anisotropic transport properties, and optimal device performance requires control over its preferred orientation. We find that this preferred orientation can be finely tuned through the precursor and substrate temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 40 publications
(46 reference statements)
0
52
0
Order By: Relevance
“…At the same time, the films had an open structure, which limited the shunt resistance. It was later shown the preferred orientation of the BiOI platelets grown by CVD could be controlled through the temperature of the BiI3 precursor and the temperature of the substrate [257], as discussed in Section 3.8. Growing c-axis oriented BiOI platelets resulted in compact film morphology, which improved the VOC from 0.7 V (a/baxis oriented) to 0.9 V (c-axis oriented).…”
Section: V-vi-vii Materialsmentioning
confidence: 97%
“…At the same time, the films had an open structure, which limited the shunt resistance. It was later shown the preferred orientation of the BiOI platelets grown by CVD could be controlled through the temperature of the BiI3 precursor and the temperature of the substrate [257], as discussed in Section 3.8. Growing c-axis oriented BiOI platelets resulted in compact film morphology, which improved the VOC from 0.7 V (a/baxis oriented) to 0.9 V (c-axis oriented).…”
Section: V-vi-vii Materialsmentioning
confidence: 97%
“…This preferred orientation is favorable for charge extraction in a vertically structured device. [57] Cs 3 Sb 2 Cl x I 9-x had smaller grains (≈250 nm in size) with a lessdense morphology when grown on mesoporous TiO 2 /FTO, which we nonetheless found to allow devices with high photoconversion efficiency. [56] Critically, both BiOI and Cs 3 Sb 2 Cl x I 9-x have bandgaps close to the optimum value of 1.9 eV for IPV applications (1.93 eV for BiOI and 1.95 eV for Cs 3 Sb 2 Cl x I 9-x ), as shown in our previous works.…”
Section: Bioi and Cs 3 Sb 2 CL X I 9-x Photovoltaic Devicesmentioning
confidence: 70%
“…This preferred orientation is favorable for charge extraction in a vertically structured device. [ 57 ] Cs 3 Sb 2 Cl x I 9‐ x had smaller grains (≈250 nm in size) with a less‐dense morphology when grown on mesoporous TiO 2 /FTO, which we nonetheless found to allow devices with high photoconversion efficiency. [ 56 ]…”
Section: Resultsmentioning
confidence: 92%
“…[ 266 ] However, the mobility is highly anisotropic, and we recently showed that an a / b ‐axis preferred orientation could be achieved by controlling the growth temperature during t‐CVD growth, such that the high‐mobility planes connected the top and bottom electrodes in the photovoltaic device stack. [ 298 ] As a result, external quantum efficiencies reaching up to 80% at 450 nm wavelength were achieved in BiOI devices. [ 268 ]…”
Section: Potential Of Emerging Nontoxic Materials For Indoor Photovol...mentioning
confidence: 99%